A preclinical Talbot–Lau prototype for x‐ray dark‐field imaging of human‐sized objects. Issue 6 (27th April 2018) - Hauke, C.; Bartl, P.; Leghissa, M.; Ritschl, L.; Sutter, S. M.; Weber, T.; Zeidler, J.; Freudenberger, J.; Mertelmeier, T.; Radicke, M.; Michel, T.; Anton, G.; et al.
Abstract : Purpose: Talbot–Lau x‐ray interferometry provides information about the scattering and refractive properties of an object — in addition to the object's attenuation features. Until recently, this method was ineligible for imaging human‐sized objects as it is challenging to adapt Talbot–Lau interferometers (TLIs) to the relevant x‐ray energy ranges. In this work, we present a preclinical Talbot–Lau prototype capable of imaging human‐sized objects with proper image quality at clinically acceptable dose levels. Methods: The TLI is designed to match a setup of clinical relevance as closely as possible. The system provides a scan range of 120 × 30 cm 2 by using a scanning beam geometry. Its ultimate load is 100 kg. High aspect ratios and fine grid periods of the gratings ensure a reasonable setup length and clinically relevant image quality. The system is installed in a university hospital and is, therefore, exposed to the external influences of a clinical environment. To demonstrate the system's capabilities, a full‐body scan of a euthanized pig was performed. In addition, freshly excised porcine lungs with an extrinsically provoked pneumothorax were mounted into a human thorax phantom and examined with the prototype. Results: Both examination sequences resulted in clinically relevant image quality — even in the case of a skin entrance air kerma of only 0.3 mGy which is in the range of human thoracic imaging. The presented case of a pneumothorax and a reader study showed that the prototype's dark‐field images provide added value for pulmonary diagnosis. Conclusion: We demonstrated that a dedicated design of a Talbot–Lau interferometer can be applied to medical imaging by constructing a preclinical Talbot–Lau prototype. We experienced that the system is feasible for imaging human‐sized objects and the phase‐stepping approach is suitable for clinical practice. Hence, we conclude that Talbot–Lau x‐ray imaging has potential for clinical use and enhances the diagnostic power of medical x‐ray imaging.